Proceedings of 35th International Cosmic Ray Conference — PoS(ICRC2017) 2017
DOI: 10.22323/1.301.0111
|View full text |Cite
|
Sign up to set email alerts
|

What is Causing the Deficit of High-Energy Solar Particles in Solar Cycle 24?

Abstract: The number of large Solar Energetic Particle (SEP) events in solar cycle 24 is reduced by a factor of about 2 compared to cycle 23. In the first 8 years of this cycle there have been only 38 "GOES" proton events compared to 79 at this point of cycle 23. What is less well known is that the fluence of protons and heavier ions is reduced by even greater factors (by 6 times for greater than 10 MeV protons, and by 9 times for greater than 100 MeV protons). Indeed the spectral breaks for H, O, and Fe are all occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Furthermore, it has to be noted that the vast majority of these major SEP events did occur in solar cycle 23 clearly underlining the unusual weak character of cycle 24 (Richardson et al, ). Similar effects have been also observed for the contribution to the fluence in previous studies (Mewaldt et al, , ).…”
Section: Long‐term Data Analysissupporting
confidence: 90%
“…Furthermore, it has to be noted that the vast majority of these major SEP events did occur in solar cycle 23 clearly underlining the unusual weak character of cycle 24 (Richardson et al, ). Similar effects have been also observed for the contribution to the fluence in previous studies (Mewaldt et al, , ).…”
Section: Long‐term Data Analysissupporting
confidence: 90%
“…While some of the largest events in cycle 24 were not directed toward Earth, for example, 23 July 2012 and 1 September 2014, even including the STEREO observations in the top 10 list (Table ) does not change the conclusion that the conditions of cycle 23 yielded larger SEP events (on average a factor of 2.4 bigger). As suggested by Mewaldt et al () this may be a result of the lower interplanetary density of suprathermal seed particles, combined with a lower magnetic field strength in cycle 24 (see also Gopalswamy, Akiyama, et al, ; Vainio et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Several aspects of cycle 24 have been shown to be significantly weaker than those of cycle 23, including the solar wind speed and the magnetic field strength (see, e.g., McComas et al, ). The number of large SEP events is no exception (Gopalswamy, Akiyama, et al, ; Mewaldt et al, ), with the decrease in GLE events being particularly strong (two in cycle 24 vs. 16 in cycle 23; gle.oulu.fi). In this paper we focus not only on the most recent GLE event on 10 September 2017, comparing its properties to the GLE events of cycle 23 and the other cycle 24 event of 17 May 2012, but also present data from the extreme SEP events observed by STEREO and discuss the top 10 SEP events of cycles 23 and 24.…”
Section: Introductionmentioning
confidence: 99%
“…What are the ultimate causes for that? [54] identified that the present cycle had fewer fast CMEs and a weaker magnetic field. Such effects are amplified by the nonlinear nature of the shock acceleration process: with lower suprathermal proton injection, there was weaker turbulence generation.…”
Section: Spectra (5)mentioning
confidence: 78%
“…The issue of why the present Solar Cycle 24 produced so few strong SEP events, with a much lower SEP fluence than the two preceding solar cycles (see Figure 8), was addressed by [54]. During strong events, SEP spectra have broken power laws (changing at E break ) and a high-energy rollover (at ∼ E max ).…”
Section: Spectra (5)mentioning
confidence: 96%